Research on Testing System for an Intelligent and Connected Vehicle. (June 2020) - Feng, Jiacheng; Song, Wenxuan; Zhan, Haiting; Bai, Junchao
Abstract: Due to the increase of automatic driving and network connection function, the testing system of intelligent and connected vehicle (hereinafter referred to as ICV) is quite different from traditional vehicle's. This paper presents the testing systems of ICV which based on the technology of virtual simulation, semi-physical simulation, and real vehicle test. The testing contents including automatic driving computing platform test, perception system test, network connection and information security test, HMI and ergonomics evaluation, and road test, which covers the automatic driving function, safety, comfort and reliability. The paper introduces the integration architecture and working principles of the testing systems which involves MIL, SIL, HIL, DIL and VIL. The physical relationship of each module in the system is shown by pictures. Finally, the paper summarizes the characteristics and trends of testing system and method. The ICV testing architecture proposed in this paper offers reference for the construction of related laboratories and provide guarantee for ICV application.